Gastronomy for Tourism Development Potential of the Western Balkans. - Pestek, Almir (Emerald Publishing Limited, 2020)
Gastronomy for Tourism Developmentprovides readers with insight into the political reasons all countries in the region pay little attention to the common gastronomic heritage. It challenges the issues faced by those within the industry, addressing the potential for the region to become a sustainable and attractive European food destination.